Sources of increased wage differentials in the Finnish private sector - Rita Asplund (The Research Institute of the Finnish Economy (ETLA), 2009)
This paper explores the sources underlying the marked increase in the dispersion of private-sector wages in Finland since the mid-90s by use of a recently proposed method to decompose changes along the whole wage distribution over a period of time into several factors contributing to those changes. The results suggest that changes in the way individual and workplace attributes are valued in the labour market have been the driving force behind both real wage growth and increasing wage dispersion. This finding holds true most strongly for white-collar manufacturing workers, who dominate the higherpaid segment of the Finnish private sector. This phenomenon is less pronounced for services sector workers and, eventually, disappears when moving towards the lower end of the sector's wage distribution. Taken together, these findings are well in line with international evidence stating that changes in the way attributes are rewarded in the labour market tend to drive the growth in wage dispersion in the upper tail of the distribution while changes in the workforce composition are likely to be a notably stronger force behind widening wage differentials in the lower tail of the distribution.
Keywords: J31; 330; decomposition; composition effect; price effect; wage dispersion; Lohndifferenzierung; Privatwirtschaft; Dekompositionsverfahren; Finnland